2010
DOI: 10.1177/1933719110361960
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Expression of Cyclooxygenase 2 in Preeclampsia

Abstract: The objective of this study was to determine: 1) if neutrophils of preeclamptic women express cyclooxygenase-2 (COX-2), and 2) if COX-2 mediates neutrophil interleukin-8 (IL-8) production. Neutrophils were isolated from heparinized blood collected from women with preeclampsia and normal pregnancy, and from normal nonpregnant women. COX-2 protein was measured in the neutrophils of the three groups by specific ELISA. To study the role of COX-2 in IL-8 production, neutrophils of normal pregnant women were activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…COX-2 is the important rate-limiting enzyme that is synthesized by prostaglandin (PG), which is associated with inflammation and atherosclerosis ( 18 ). PG is a type of important tissue-derived medium, and the vasoactive PG products, such as angiotensin and thromboxane, play key roles in vascular endothelial injury and thrombosis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is the important rate-limiting enzyme that is synthesized by prostaglandin (PG), which is associated with inflammation and atherosclerosis ( 18 ). PG is a type of important tissue-derived medium, and the vasoactive PG products, such as angiotensin and thromboxane, play key roles in vascular endothelial injury and thrombosis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, neutrophils obtained from pre-eclamptic females express significantly more COX-2 than healthy pregnant females or healthy non-pregnant females. 17 Another theory proposed that the activation of neutrophils occurs in placental circulation under hypoxic conditions that contribute to increased vascular resistance in pre eclamptic pregnancies. 18 It was also found that there was more neutrophil endothelial adhesion and infiltration into intimal space in systemic vasculature while lymphocyte infiltration was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, COX-2 and mPGES-1 may induce muscle pain through PGE 2 production. In inflammation, COX-2 is expressed in neutrophils, macrophages, endothelial cells, and muscle nuclei/muscle satellite cells [ 11 , 27 , 28 ]. mPGES-1 has been reported to be localized in macrophages and fibroblasts during inflammation [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%